Final analysis of a phase I/IIa trial of the folate‐binding protein‐derived E39 peptide vaccine to prevent recurrence in ovarian and endometrial cancer patients. (5th July 2019) - Brown, Tommy A.; Byrd, Kevin; Vreeland, Timothy J.; Clifton, Guy T.; Jackson, Doreen O.; Hale, Diane F.; Herbert, Garth S.; Myers, John W.; Greene, Julia M.; Berry, John S.; Martin, Jonathan; Elkas, John C.; et al.
Abstract: Background: E39, an HLA‐A2‐restricted, immunogenic peptide derived from the folate‐binding protein (FBP), is overexpressed in multiple malignancies. We conducted a phase I/IIa trial of the E39 + GM‐CSF vaccine with booster inoculations of either E39 or E39′ (an attenuated version of E39) to prevent recurrences in disease‐free endometrial and ovarian cancer patients(pts). Here, we present the final 24‐month landmark analysis. Patients and methods: HLA‐A2 + patients receiving E39 + GM‐CSF were included in the vaccine group (VG), and HLA‐A2‐ pts (or HLA‐A2 + patients refusing vaccine) were followed as the control group (CG). VG group received 6 monthly inoculations as the primary vaccine series (PVS) and were randomized to receive either E39 or E39′ booster inoculations. Demographic, safety, immunologic, and disease‐free survival (DFS) data were collected and evaluated. Results: Fifty‐one patients were enrolled; 29 in the VG and 22 in the CG. Fourteen patients received <1000 μg and 15 received 1000 μg of E39. There were no clinicopathologic differences between VG and CG or between dose groups. E39 was well tolerated. At the 24 months landmark, DFS was 55.5% (VG) vs 40.0% (CG), P = 0.339. Patients receiving 1000 μg and boosted patients also showed improved DFS ( P < 0.03). DFS was improved in the 1000 μg group after treatment of primary disease (90.0% vs CG:42.9%, P = 0.007), but not in recurrent patients. In low‐FBP expressing patients, DFS was 100.0% (1000 μg), 50.0% (<1000 μg), and 25.0% (CG), P = 0.029. Conclusions: This phase I/IIa trial reveals that E39 + GM‐CSF is safe and may be effective in preventing recurrence in high‐risk ovarian and endometrial cancer when optimally dosed (1000 μg) to FBP low patients being treated for primary disease. Abstract : The folate binding protein derived E39 peptide vaccine is safe, and may improve disease‐free survival in clinically disease‐free ovarian and endometrial cancer patients, especially in those with primary disease and low FBP expression. These results will help determine the population of further studies of E39, and subgroup analyses have broader implications for peptide vaccines.